Seroprevalence of SARS-CoV-2 Antibodies in Children and Adolescents: Results From a Population-Based Survey in 10 Colombian Cities - Marcela María Mercado-Reyes MSc; Marcela Daza MD; Angélica Pacheco MPH; María Ximena Meneses-Gil MSc; Marisol Galindo MPH; Jenssy Catama MS; Luz Stefany Botero MSc; Lyda Muñoz MS; German Quinche MD; Martha Lucía Ospina MD (SAGE Publishing, 2022)
Background. Understanding COVID-19 dynamics in Colombia during the first pandemic year (2020) gives important insights surrounding population's exposure risk and specific susceptibilities. Seroprevalence studies can aid in having a broader understanding of the disease, offering a more inclusive view of the pandemic's impact across the population. Methods. A population-based cross-sectional study to assess antibodies against SARS-CoV-2 in 10 Colombian cities was developed between September and December 2020. Cities were grouped according development typology (Robust (RD), Intermediate (ID) and Incipient (InD)). Detection of total antibodies (IgM + IgG) against SARS-CoV-2 was employed. Univariate Odds Ratios (OR) were estimated for antibody results and selected variables. Results . About 3124 children aged between 5 and 17 years were included. Factors related to lower seropositive results were affiliation to the employer-based health insurance in RD and ID cities (OR: 0.579, 95% CI 0.477-0.703, OR: 0.648, 95%CI 0.480-0.874 respectively) and living in a household with adequate access to public services only for ID cities (OR: 0.679. 95% CI 0.491-0.939). Higher seropositivity rates in RD and ID cities were seen in children belonging to the low socioeconomic stratum (RD: OR: 1.758, 95% CI 1.427-2.165; ID: OR: 2.288, 95% CI 1.599-3.275) and living in an overcrowded household (RD: OR: 1.846, 95% CI 1.467-2.323; ID: OR: 2.379, 95% CI 1.769-3.199). Conclusions. Children and adolescents showed substantial impact from the COVID-19 pandemic. Disadvantageous living conditions were found to be significantly related to having a positive SARS-CoV-2 antibody test. These results highlight the need to prioritize vulnerable populations in the context of health emergencies.